The ideological scramble for Africa : how the pursuit of anticolonial modernity shaped a postcolonial order, 1945-1966 - Gerits, Frank (Cornell University Press, 2023)
"After 1945 African nationalists were drawn into a battle for African hearts and minds. Rather than choose between East or West, Kwame Nkrumah of Ghana promoted a vision of anticolonial modernity and competed with imperial, communist, and capitalist modernization schemes to prove the superiority of his plan for postcolonial order"--